Effects of boron nitrite in thermoplastic polyurethane on thermal, electrical and free volume properties - TAV, CUMALİ; DUMLUDAĞ, FATİH; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH; YAHŞİ, UĞUR (SPRINGER, 2019)
The effects of various filler amounts of boron nitride (BN) on surface morphology, DC and AC conductivity and free volume properties of thermoplastic polyurethane (TPU) were investigated using FTIR, TGA, DSC, SEM, PALS and conductivity (DC and AC) measurements. The free volume properties, electrical measurements and surface morphology of TPU/BN were found to be dependent on temperature and weight percentages of BN content. When one weight percentage of BN was added in TPU, the glass transition temperature jumped to 69.42 degrees C from -1 degrees C. Increasing BN weight percentages caused the glass transition temperature of the TPU/BN composites to decrease slightly. Morphological measurements indicated that agglomerations occurring throughout the TPU/BN composites did not cause remarkable effects on their thermal stabilities. Orthopositronium lifetime (or free volume) and intensity increased significantly as a function of temperature, but with respect to BN weight percentages in TPU, they showed a peak with a highest value at about 2% BN content. Similarly, DC and AC conductivity measurements were carried out on TPU with and without BN content at temperatures ranging from 23 to 105 degrees C in dark under vacuum and in the frequency range of 40Hz-100kHz. The DC and AC conductivity values with increasing BN weight percentages showed the similar behavior as free volume fraction that had a peak at about 2% BN content.
Keywords: Conducting polymers; TPU; BN; Free volume; Positron annihilation lifetime spectroscopy; DC and AC conductivity; POSITRON-ANNIHILATION; MORPHOLOGY; CONDUCTIVITY; TEMPERATURE; DEPENDENCE; COMPOSITE; POLYMER